Prestack seismic prediction of sandstone reservoirs in the fifth member of Xujiahe Formation in Dongfengchang area of Ziyang - ZHENG Gongying, LYU Qibiao, YANG Yongjian, XU Shoucheng (Youqicang pingjia yu kaifa)
In the Dongfengchang area of Ziyang, the fifth member of Xujiahe Formation exhibits multiple phase of superimposed channels with rapid facies changes in the channel sandstones. The reservoirs are highly heterogeneous, with minimal differences in impedance between sandstones and mudstones. The seismic response characteristics of the reservoirs are multifaceted. Additionally, the pre-stack seismic data quality is suboptimal, compounded by an absence of shear wave logging data. In the preliminary stages, conventional post-stack attributes were used to characterize the boundaries of channel sand bodies and the distribution of high-quality reservoirs, but the accuracy of this characterization was limited. To address the mentioned challenges, high-quality pre-stack seismic data was obtained through noise suppression, data flattening, and optimal frequency enhancement techniques. An improved XU-WHITE model-based approach was utilized to predict shear wave velocities. Innovative indicators based on rock physics analysis were developed, and a seismic prediction volume for lithology and reservoir properties was obtained through simultaneous inversion of three pre-stack parameters. This approach allowed for a detailed characterization of sand body boundaries and distribution. In favorable facies zones, using property prediction attributes, the distribution of “sweet spots” within tight sandstone reservoirs was predicted. The research results indicate the following: ①High-fidelity pre-stack data optimization processing provides reliable and AVO-compliant pre-stack data, establishing a solid foundation for subsequent pre-stack inversion; ②The improved XU-WHITE model-based shear wave velocity prediction technique yields more accurate shear wave velocities, which are beneficial for rock physics analysis; ③The construction and inversion techniques of lithology and physical property indicator factors are effective in achieving a precise characterization of the lithology and physical properties of tight sandstone reservoirs. This technology has shown promising results in characterizing the tight sandstone reservoirs and predicting “sweet spots” in the Xujiahe Formation gas reservoirs in Ziyang. It holds potential for broader applications in similar geological settings.